Le nouveau Xinjiang : intégration et recompositions territoriales d’une périphérie chinoise - Alain Cariou (EchoGéo)
This paper analyses recent geographic change in the Xinjiang Uygur Autonomous Region. Xinjiang plays a geostratégic role in China due to abundance of natural resources such as oil, gas an coal but also for its particular geographic location in the heartland of Central Asia. The area gives to China an high potentiel for trade with the newly independent Central Asian republics and Eurasia. That’s the reason why central government take active measures for an acceleration of the economic development in the region with the aim of promoting regional security, cultural and économic integration. Nowadays, an unprecedent change taken place in Xinjiang with the improvements in transportation infrastructure. The expansion of the transcontinantal railway and highways between Est China to Central Asia has created a fast growing economies and the increase of Han migration. The rapide decline of the proportion of ethnic minority nationality is the result of a political strategy of Chinese national expansion and territorial intergation in order to control the Xinjiang.